Lymphocytic Esophagitis With CD4 T-cell–predominant Intraepithelial Lymphocytes and Primary Esophageal Motility Abnormalities: A Potential Novel Clinicopathologic Entity. (November 2015) - Xue, Yue; Suriawinata, Arief; Liu, Xiaoying; Li, Zhongze; Gabbard, Scott; Rothstein, Richard; Lacy, Brian; Lisovsky, Mikhail
Abstract : Lymphocytic esophagitis (LE) is an uncommon poorly defined histologic pattern. Its significance is largely unknown. The goal of our study was to characterize LE clinically, histologically, and immunophenotypically. Biopsies of 45 patients with LE and no intraepithelial granulocytes were selected throughout a 36-month period during routine diagnostic work. After reevaluation, complete absence of intraepithelial granulocytes was confirmed in 21 patients (LE-NG group), and few granulocytes were found in 24 patients (LE-FG). The control group consisted of 28 patients with active esophagitis consistent with reflux and overtly increased intraepithelial lymphocytes (REIL). The ratio of CD4:CD8 intraepithelial lymphocytes (IEL)>1 indicated predominance of CD4 IEL; the ratio ⩽1 indicated predominance of CD8 IEL. Dysphagia was the primary complaint in 71%, 54%, and 39% of the patients with LE-NG, LE-FG, and REIL, respectively ( P =0.04, LE-NG vs. REIL). Importantly, primary esophageal motility abnormalities were found in 10/11 (91%) tested LE-NG patients, 6/10 (60%) LE-FG patients, and 6/11 (54%) REIL patients. CD4 IELs were predominant in 81%, 50%, and 39% of LE-NG, LE-FG, and REIL cases, respectively ( P =0.004, LE-NG vs. REIL), and in 90%, 83%, and 88% of the cases with primary motility abnormalities from the same groups. The prevalence of primary motility abnormalities was significantly higher in patients with CD4-predominant esophagitis than in patients with CD8-predominant esophagitis from all groups (21/24 [83%] vs. 2/8 [25%], P =0.005). A distinctive type of LE with predominance of CD4 IEL is associated with primary motility abnormalities suggesting a diagnostic utility of evaluating CD4 and CD8 subpopulations of T cells in LE. Abstract : Supplemental Digital Content is available in the text.